Effects of Calcium and Copper on Lignin Biosynthesis and Suppression of Ganoderma Boninense Infection in Oil Palm Seedlings - Ahmad Azmi, Nur Sabrina (2011)
Ganoderma boninense the causal pathogen of Basal Stem Rot (BSR) disease is a white rot basidiomycetous fungus. The pathogen infects oil palm (Elaeis guineensis Jacq.) mainly through its roots and degrade the lignin component of wood leaving white cellulose exposed. Therefore, by understanding the mode of infection of G. boninense on oil palm, the ideal solution to slow down the emergence of basal stem rot disease is to enhance the oil palm physical barriers through lignin biosynthesis by calcium (Ca) and copper (Cu) supplementation. The objectives of our study are to find the best concentration of Ca and Cu that gives optimum production of lignin and to evaluate its effects towards suppressing BSR incidence. Copper have been reported to enhance the production of lignin-related enzymes in plants, and meanwhile, calcium plays a major role in cell wall stiffening. The experiment was carried out to investigate changes in peroxidase activity, laccase activity, hydrogen peroxide concentration and lignin content in roots of Ca-supplemented and Cu-supplemented oil palm seedlings and their relationships with lignification. 3-month-old oil palm seedlings were supplemented with either Ca or Cu ions (in half- strength Hoagland nutrient solution) in sand culture for 3 months. Ca and Cu-supplemented oil palm seedlings showed significant enhancement in peroxidase activity, laccase activity and lignin content. The amount of hydrogen peroxide was the lowest in 2 mg/L Cu- supplemented tissues among Cu- supplemented tissues and 4000 mg/L Ca- supplemented tissues was the lowest (17.7%, 20.5% respectively) among Ca- supplemented tissues 3 months after supplementation. The peroxidase activity was increased significantly in 2 mg/L Cu (49.0%) among Cu- supplemented tissues and in 4000 mg/L Ca (72.1%) among Ca- supplemented tissues 3 months after supplementation. Laccase activity in 2 mg/L Cu (41.9%) and 4000 mg/L Ca (130.3%) and lignin content in 2 mg/L Cu (61.1%) and 4000 mg/L Ca (86.2%) were also significantly high compared to other treatments. Scanning electron microscopy observations of Cu and Ca-supplemented tissues showed the thickest cell wall (5.55 μm and 6.01 μm respectively) between two adjacent parenchyma cells after 3 months supplementation. The concentrations that give optimum production of lignin content, which are 2 mg/L Cu and 4000 mg/L Ca were chosen to investigate its effect on suppressing the BSR disease. The oil palm seedlings were supplemented with Ca and Cu either singly or as mixture for three months before challenged with Ganoderma boninense. The experiment was carried out to determine whether high lignin content in the roots can suppress the infection and spread of Ganoderma. Results showed that supplementation with mixture of 2 mg/L Cu with 4000 mg/L Ca gave the best suppression of BSR based on the lowest epidemic rate and highest percentage of disease reduction which suggested that it was effective in suppressing Ganoderma infection in oil palm.